2017
DOI: 10.1108/er-01-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational learning in soft regulation of workplace gender equality

Abstract: Purpose The purpose of this paper is to explain progress, or the lack of it, in achieving workplace gender equality goals prescribed by affirmative action regulation by using concepts from soft regulation and organizational learning. Design/methodology/approach The research design is a longitudinal study (2002-2012) of a critical case, that of a single large organization in the male-dominated steel manufacturing, distribution and mining industries. The case focusses on the evidence about organizational learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Public sector equality duties have been found to have a normative impact, spreading ideas and strategies about equality from the public to the private sector. However, some researchers argue that the impact of the UK gender equality duty has been tempered due to weak enforcement measures and a focus on process rather than outcomes (Manfredi et al, 2018; Conley and Page, 2015). Manfredi et al (2018) recommended that a positive gender equality duty can be strengthened through effective data collection, education, leadership and strong enforcement mechanisms.…”
Section: Where To Next?mentioning
confidence: 99%
See 2 more Smart Citations
“…Public sector equality duties have been found to have a normative impact, spreading ideas and strategies about equality from the public to the private sector. However, some researchers argue that the impact of the UK gender equality duty has been tempered due to weak enforcement measures and a focus on process rather than outcomes (Manfredi et al, 2018; Conley and Page, 2015). Manfredi et al (2018) recommended that a positive gender equality duty can be strengthened through effective data collection, education, leadership and strong enforcement mechanisms.…”
Section: Where To Next?mentioning
confidence: 99%
“…However, some researchers argue that the impact of the UK gender equality duty has been tempered due to weak enforcement measures and a focus on process rather than outcomes (Manfredi et al, 2018; Conley and Page, 2015). Manfredi et al (2018) recommended that a positive gender equality duty can be strengthened through effective data collection, education, leadership and strong enforcement mechanisms. Enforcement powers could mirror those in labour law and workplace health and safety, supported by inspectorates, audit institutions, and ombudsman's offices, as recommended by the OECD (2019).…”
Section: Where To Next?mentioning
confidence: 99%
See 1 more Smart Citation
“…Such activities consist of welfare practices that directly influence the physical and psychological workings of employees (De Roeck et al, 2014;Potdar et al, 2018a). These encompass respect (Liu et al, 2016), training and development (Eldor and Harpaz, 2016), equality of opportunities (Macneil and Liu, 2017), work-life balance (Adisa et al, 2017), and overall wellbeing (Gupta and Sharma, 2016). Research has identified that internal CSR activities may influence employee engagement more than external CSR (Gond et al, 2017) suggesting organisations should strengthen their internal CSR practices to evoke higher employee engagement.…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…The first paper to present empirical evidence is by Macneil and Liu (2017), who problematise the relationship between soft regulation, organisational learning and workplace gender equality goals. Using a longitudinal single-case organisation in the male-dominated steel manufacturing, distribution and mining industries in Australia, the paper focuses on the evidence of organisational learning by looking at the organisation's reports to government on its activities to promote gender equality.…”
Section: Contributions To the Special Issuementioning
confidence: 99%